Diseño y Montaje De Prensa Hidráulica a Partir De Materiales Reutilizados (2024)
- The project focuses on the design and assembly of a hydraulic press intended for implementation in a metal mechanics and automotive mechanics workshop. The distinctive feature of this project lies in its innovative approach: the use of materials previously considered useless or in poor condition for the construction of the press. This initiative has the primary objective of giving a second life to these materials, thus promoting reuse and recycling in the context of the industry. The project aims to demonstrate the technical and economic feasibility of this creative and sustainable approach in industrial machinery construction. Detailed research will be carried out on the selection and preparation of the reused materials. In addition, extensive tests will be carried out to evaluate their performance and efficiency compared to traditional presses. KEYWORDS: Press, hydraulic, metal mechanics, recycling,